(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Influenced by clothing style and fit, as well as human body contour, the distribution of air gaps entrapped between human body skin and inner surface of clothing is complex and difficult to measure. The three- dimensional body scanning technology provides a realistic method to quantify the air gap volume by scanning the surface image of human body and clothing. This research measures the air gap volume of thirty experimental clothing using a 3D body scanner and analyzes the effect of clothing size and mechanical property of fabric on air gap volume under clothing. The experimental clothing is made of different fabrics with increasing chest circumference from 92 cm to 108 cm. To investigate the relationship between air gap volume and thermal property of clothing, a thermal manikin is used to measure the thermal insulations of experimental clothing. As the air gap volume increases with the garment size, the thermal insulations of clothing do not linearly increase. The thermal insulation begins to decrease when the chest circumference of experimental garments becomes more than 100 cm due to the onset of natural convection. This research is helpful to study the affecting factors of air gap volume under clothing and estimate the effect of air gap volume on the thermal property of clothing.